Political Fragmentation Indicator Database - Keane, Timothy D.; Kim, Jae Hong; Bernard, Eric (My University, 2015)
The Political Fragmentation Indicator Database is an outcome of the NSF CNH-Ex #1114931: Political Fragmentation in Local Governance and Water Resource Management project. The database contains a range of metrics that represent varying degrees of political fragmentation at multiple geographic scales. There are two files available for download. The Microsoft Access file (the “.accdb” file) contains the database and the Adobe PDF file is a detailed description of the database. The PDF file provides: 1) A description of the geographic scales, key approaches to measuring political fragmentation and effectiveness of natural resource management. 2) Descriptions of individual metrics and data sources. 3) A set of correlation analysis outcomes that explain how the metrics are interrelated with each other (at a single geographical scale or over the hierarchy) to promote appropriate uses of the data with the consideration of the interrelationships among the indicators.
Keywords: Political fragmentation; Suspended sediment; Land-use change